1997
DOI: 10.1063/1.473513
|View full text |Cite
|
Sign up to set email alerts
|

He scattering from random adsorbates, disordered compact islands, and fractal submonolayers: Intensity manifestations of surface disorder

Abstract: In the experimental-theoretical study of Ag on Pt(111), we use experimental He scattering data from low-coverage (single adsorbate) systems to determine an empirical He/Ag-Pt potential of good quality. Then, we carry out He scattering calculations for high coverage and compare with experiments for these systems. The conclusion is that the actual experimental phase corresponds to small compact Ag clusters of narrow size distribution, with partial translational disorder.2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
1
16
2
Order By: Relevance
“…2a. This correspondance between the length of the Ag adlayer rim and the TEAS specular intensity was actually expected [29], given the experimental conditions of minimal interference, but resulted actually stricter than thought.…”
Section: Resultsmentioning
confidence: 73%
“…2a. This correspondance between the length of the Ag adlayer rim and the TEAS specular intensity was actually expected [29], given the experimental conditions of minimal interference, but resulted actually stricter than thought.…”
Section: Resultsmentioning
confidence: 73%
“…Surface relaxation data measured by LEED for a pristine surface is available [20] for Cu(001). This gives a contraction between the first and second layer (i.e., d 12 ), expansion between the second and third layer (i.e., d 23 ), expansion between the third and fourth layer (i.e., d 34 ) and then normal bulk spacing. It is an oscillatory relaxation of interlayer spacings as expected for an open metal surface [21].…”
Section: Resultsmentioning
confidence: 99%
“…The very large scattering cross sections [9] of adsorbed gases (of the order of 100Å) make it possible to study the structure of adsorbate covered surfaces, migration of low-coverage adsorbates on surfaces. Similarly, large cross sections (of the order of 12Å) [10,11] for diffuse helium scattering from steps on metal surfaces enables us to characterize randomly stepped surfaces and to study the epitaxial growth processes [12]. Experimental studies have shown that the magnitude of step edge cross section for different metal surfaces are rather large compared to the atomic dimension of the crystal face [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…More recent efforts have concentrated on potentials for scattering from various adsorbed monolayers on metals, e.g., the c(2 * 2) phase of oxygen on Ni(001) [10], hydrogen-plated Pt [11], and Xe/Cu(110) [12]. We recently fitted cross-section data to obtain a potential for a disordered Ag/Pt(111) system [13]. A very detailed recent review of potentials of physical adsorption is the work of Vidali et al [14], which tabulates parameters of interest as deduced from analysis of experimental data and calculations of over 250 gas-surface systems, including He.…”
Section: Introductionmentioning
confidence: 99%